Power loss minimization through maximal power endurance or repeated power training programs - Gonzalo-Skok, O.; Tous-Fajardo, J. (International Journal of Sports Physiology and Performance, 2025)
Purpose: The present study analyzed the effects of a maximal-power-endurance (MPE) versus a repeated-power-ability (RPA) training program on different strength, power, and repeated-power measurements in a short- and long-term training period and the relationships between changes in all variables.